Surface‐modified mesoporous silica nanorods for the highly aging resistance rubber through controlled release of antioxidant. (2nd June 2021) - Luo, Yang; Wang, Jun‐Peng; Cui, Xurui; Fu, Ye; Li, Guo Liang; Wang, Wencai
Abstract : The migration and blooming of antioxidant molecules in the field of anti‐aging rubber is a challenge, where developing novel nanocarriers loaded with antioxidant molecules can solve the above problem. In this article, the surface thiol functionalized mesoporous silica nanorods loaded with antioxidant N‐(1, 3‐dimethyl)butyl‐N′‐phenyl‐p‐phenylenediamine (MSN‐SH‐4020) was synthesized to avoid the blooming of antioxidants and then to improve the anti‐aging performance of styrene‐butadiene rubber (SBR). The migration of antioxidant molecules could be limited by encapsulating antioxidant in the pore of mesoporous silica nanorods, and the contend of antioxidant in the SBR reaches up to 1.33 wt%. The sustained release of antioxidant molecules from the pore increases the effective time of action of the antioxidant. After 168 hours of thermal oxidative aging test at 100°C, styrene‐butadiene rubber with 10 wt % surface thiol functionalized mesoporous silica nanorods loaded with 4020 (MSN‐SH‐4020) shows preservation of mechanical properties without blooming. This approach is highly perspective in many applications, such as long‐life sealing rubber and conveyor belts.